Connection Knowledge with Application Safety Health Work Automotive Engineering Education Student Makassar State University - Rahman Pance; Mohammad Ahsan S. Mandra; Darmawang Darmawang; Muhammad Yahya (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
Makassar State University Automotive Engineering Education conducts occupational health and safety programs in accordance with legal regulations. However, in fact, even as of 2019, many students did not take labor protection measures when performing welding work in the laboratory, and as a result, many people had eye pain after welding. The purpose of this study was to explain the occupational safety and health knowledge of students in the Automotive Engineering Education Laboratory of Makassar State University, explain the application of occupational safety and health, and explore the relationship between the knowledge of occupational safety and health and the application of occupational safety and health. to find out. This type of study uses observational data collection techniques, and quantitative descriptive methods using questionnaires processed through the SPSS application. The study population consisted of only his 2019 automotive engineering students, and his sample was 39 from Harry King's nomogram formula. As a result, the correlation coefficient, rCount was 0.466 and the obtained significance value was 0.003. The correlation coefficient of rTable with N=39 is 0.466 and the error rate is 5% (0.05). The rCount value of 0.466 is greater than the rTable = 0.316. This means that there is a positive and significant correlation between theoretical knowledge of OSH and the application of OSH.